Myiasis Telinga pada Lansia – Sebuah Laporan Kasus: Laporan Kasus - Febriani, Ridha Patria; Ruspita, Dian Ayu; Halleyantoro, Ryan (PT Kalbe Farma Tbk., 2026)
Introduction: Aural myiasis is a rare parasitic infestation in the external ear canal caused by fly larvae. It is commonly observed in tropical and subtropical regions, with risk factors including poor hygiene, chronic illnesses, and occupational exposure to environments infested with flies. Case: A 72-year-old male from a rural village presented with complaints of severe pain in his right ear, accompanied by bloody discharge, and a sensation of movement in the ear canal. Multiple removal procedures were finally succeeded in extracting all infesting larvae. The patient was treated with antibiotics, analgesics, and antiseptic irrigation. Discussion: Aural myiasis poses a health risk, especially in geriatric and rural populations. Delayed treatment can lead to extensive tissue damage and secondary infections. Conclusion: Diagnosis is made by identifying dipteran larvae in infested body parts. Comprehensive management involves mechanical removal, pharmacological treatment,and preventive education. Increased awareness among healthcare providers is essential to reduce morbidity associated with aural myiasis.